Sintesis Nanopartikel Poly(NIPAM) Polimer untuk Pemurnian Enzim Protease dengan Teknik Afinitas Presipitasi - Munir Mukhlisin; Risky Rivaldy; Syaubari Syaubari; Muhammad Faisal (Universitas Syiah Kuala, 2020)
Currently, the biospecific affinity method for separation has gain attention and is continuously being developed. Precipitation affinity techniques continue to be developed because of it’s simplicity economic value without reducing the purity of the product and the recoverable polymer can be reused And easy to scale-up. The polymer used for the precipitation affinity has a ligand group that can work specifically therefore named